2013
DOI: 10.1161/circulationaha.112.000230
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transendocardial and Intracoronary CD34 + Cell Transplantation in Patients With Nonischemic Dilated Cardiomyopathy

Abstract: A fter an acute myocardial injury, recruitment of stem cells may significantly influence the repair process. Studies have shown that serum stromal-derived factor-1 (SDF-1) levels rise significantly after an acute myocardial infarction, which increases homing of stem cells to the damaged tissue. 1 In contrast, in patients with chronic heart failure, local homing signals may be less intense. This difference is especially pronounced in patients with nonischemic dilated cardiomyopathy (DCM), which involves signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 172 publications
(133 citation statements)
references
References 25 publications
5
126
1
1
Order By: Relevance
“…When direct intramuscular/ subendocardial injection of stem cells is used under the guidance of electrophysiological lv mapping, using noGa ® xP Cardiac navigation system (Biologics delivery systems, irwindale, Ca), significantly higher stem cell retention rates are achieved (up to approximately 10%). 26 our findings confirm those from preclinical models that directly compared different methods of stem cell delivery, showing the direct intramuscular route to be superior.…”
Section: Evaluation Of Early Retentionsupporting
confidence: 85%
“…When direct intramuscular/ subendocardial injection of stem cells is used under the guidance of electrophysiological lv mapping, using noGa ® xP Cardiac navigation system (Biologics delivery systems, irwindale, Ca), significantly higher stem cell retention rates are achieved (up to approximately 10%). 26 our findings confirm those from preclinical models that directly compared different methods of stem cell delivery, showing the direct intramuscular route to be superior.…”
Section: Evaluation Of Early Retentionsupporting
confidence: 85%
“…Overall Jehn et al 50 Radke et al 24 Alahdab et al 18 Alahdab et al 18 Rostagno et al 13 Rostagno et al 45 Ingle et al 26 Jehn et al 36 Ingle et al 26 Deuschle et al 52 Rostagno et al 46 Bagur et al 48 Zugck et al 21 Pepera et al 32 Goode et al 18 Deuschle et al 52 Faggiano et al 47 Leszek et al 35 Rostagno et al 13 Goode et al 7 Zugck et al 21 Ingle et al 26 Ingle et al 26 Rostagno et al 45 Tay et al 49 Jankowska et al 29 Bagur et al 48 Ates et al 30 Rostagno et al 46 Gary et al 25 Jehn et al 36 Karavidaset al 28 Souza et al 53 Jehn et al 50 Bosnak Güçlü et al 27 Alahdab et al 18 Forman et al 20 Zaidi et al Goscinska-Bis et al 37 Alahdab et al 18 Forman et al 20 Keast et al 31 Vrtovec et al 51 Rostagno et al 45 Souza et al 53 Tay et al 49 Jaski et al 34 Zugck et al …”
Section: Discussionmentioning
confidence: 99%
“…Disease progression in DCM affects both ventricles, and right ventricular (RV) dysfunction represents an important adverse prognostic factor 2, 3. Although several clinical trials have demonstrated that left ventricular dysfunction in DCM can be partially reversed by cell therapy 4, 5, 6, 7, no study to date investigated the effects of this approach on RV. Thus, the aim of the present study was to investigate the effects of transendocardial CD34 + cell therapy on RV function in patients with DCM.…”
Section: Introductionmentioning
confidence: 99%